2012
DOI: 10.3109/15563650.2012.659252
|View full text |Cite|
|
Sign up to set email alerts
|

Acetaminophen and acetylcysteine dose and duration: Past, present and future

Abstract: Acetylcysteine has been utilized successfully in the treatment of acetaminophen overdose since the 1970s. Although prospective trials as to efficacy and safety of acetylcysteine were conducted, there were no randomized controlled trials. This commentary addresses the reasons for this, and the background to choice of dose of acetylcysteine utilized in the oral and IV dosing regimens. Nomograms to predict possible hepatotoxicity based upon time of ingestion of acetaminophen were developed from a relatively arbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(152 citation statements)
references
References 36 publications
2
141
0
9
Order By: Relevance
“…N-acetylcysteine (NAC) has been available for decades and is extremely effective at managing and preventing acute injury to acetaminophen overdose (243,245). Oral and IV formulations appear equally effective (246) The use of liver assist devices such as molecular adsorbent recirculating systems ( MARS) or plasma exchange have proven effective as a bridge to transplant, but remain largely investigational (68,69,(251)(252)(253).…”
Section: Treating Dilimentioning
confidence: 99%
“…N-acetylcysteine (NAC) has been available for decades and is extremely effective at managing and preventing acute injury to acetaminophen overdose (243,245). Oral and IV formulations appear equally effective (246) The use of liver assist devices such as molecular adsorbent recirculating systems ( MARS) or plasma exchange have proven effective as a bridge to transplant, but remain largely investigational (68,69,(251)(252)(253).…”
Section: Treating Dilimentioning
confidence: 99%
“…The rationale was that 150 mg was half the concentration of 300 mg/L, which at that time was believed to cause death. 12 Subsequent reports have found that deaths can occur in untreated patients at concentrations below the 200 mg/L line and, in very rare patients who are fasting, even below 100 mg/L. 5,13,14 In the 1990s, the United Kingdom changed its policy to include a risk assessment in those patients with paracetamol concentrations between the 100 and 200 mg/L nomograms.…”
Section: Problems With the Paracetamol Nomogramsmentioning
confidence: 99%
“…The dose of acetylcysteine is likely to be excessive as a glutathione replacement for all but the largest of paracetamol overdoses, that is, with concentrations 4500 or 600 mg/L. 12 Some have suggested it might be possible to model acetylcysteine requirements based on estimated paracetamol dose, but this has yet to be tested in practice. 33 …”
Section: Dn Batemanmentioning
confidence: 99%
“…The administration of an additional NAC bolus or extending the duration of the 6.25 mg/kg/h infusion may be appropriate in certain clinical scenarios [13][14][15][16]. Treatment beyond 21 h is indicated when patients have evidence of hepatotoxicity evidenced by elevations in aminotransferases, abnormalities in predictors of poor prognosis, or persistent APAP detected by laboratory testing.…”
Section: Disclaimermentioning
confidence: 99%